The Presence of Androgen Receptor Elements Regulates ZEB1 Expression in the Absence of Androgen Receptor. Issue 1 (January 2015) - Mooney, Steven M.; Parsana, Princy; Hernandez, James R.; Liu, Xin; Verdone, James E.; Torga, Gonzalo; Harberg, Calvin A.; Pienta, Kenneth J.
Abstract Zinc finger E‐box binding homeobox 1 (ZEB1) is a transcription factor that plays a central role in the epithelial to mesenchymal transition (EMT) of cancer cell lines. Studies on its regulation have mostly focused on the negative 3'UTR binding of miR200c. Interestingly, it has been previously reported that androgen receptor (AR) regulates ZEB1 expression in breast and prostate cancers. In order to validate this, various ZEB1 promoter deletions were cloned into a luciferase reporter system to elucidate the contribution of two putative androgen response elements (AREs). The in vivo contribution of AR was also assessed in cell lines after R1881 treatment using qPCR with prostate specific antigen (PSA) as the positive control. We discovered that AR upregulates the levels of expression of ZEB1 10‐fold on a luciferase promoter that only contains the distal ARE. However, when the proximal ARE is included, no additional activation is apparent with AR or its hormone independent variant, AR‐V7. Furthermore, we demonstrate here that a promoter construct containing both AREs activates transcription of ZEB1 even in the AR‐null cell lines DU145 and PC3. Incubation of the AR‐positive cell line, LNCaP with R1881, failed to substantially increase the expression levels of ZEB1. Despite the presence of AREs in the promoter region, it appears that ZEB1 expression can be induced even without AR. In addition, the region around the distal ARE is a potent repressor in AR‐null cell lines. J. Cell. Biochem. 116: 115–123, 2015. © 2014 Wiley Periodicals, Inc.